On-Surface Synthesis and Determination of the Open-Shell Singlet Ground State of Tridecacene - Zuzak, Rafal; Kumar, Manish; Stoica, Otilia; Soler-Polo, Diego; Brabec, Jiri; Pernal, Katarzyna; Veis, Libor; Blieck, Remi; Echavarren, Antonio M; Jelinek, Pavel; Godlewski, Szymon (Angewandte Chemie (International ed. in English), 2024)
The character of the electronic structure of acenes has been the subject of longstanding discussion. However, convincing experimental evidence of their open-shell character has so far been missing. Here, we present the on-surface synthesis of tridecacene molecules by thermal annealing of octahydrotridecacene on a Au(111) surface. We characterized the electronic structure of the tridecacene by scanning probe microscopy, which reveals the presence of an inelastic signal at 126 meV. We attribute the inelastic signal to spin excitation from the singlet diradical ground state to the triplet excited state. To rationalize the experimental findings, we carried out many-body ab initio calculations as well as model Hamiltonians to take into account the effect of the metallic substrate. Moreover, we provide a detailed analysis of how the dynamic electron correlation and virtual charge fluctuation between the molecule and metallic surface reduces the singlet-triplet band gap. Thus, this work provides the first experimental confirmation of the magnetic character of tridecacene.
Keywords: Diradicals; Higher Acenes; Inelastic Excitation; Open-Shell Compounds; Many-Body Calculations